Alternatives to continuous positive airway pressure treatment in sleep apnoeas and hypopnoeas syndrome related to myofunctional and postural reeducation therapy: protocol for a systematic review - Montserrat Solera-Martínez; Blanca Notario-Pacheco; Rocio Palomo-Carrión; Marta Maria Guijarro-Herráiz; Natalia María Arias-Palencia; Lidia Lucas- de la Cruz; Beatriz Guijarro-Herráiz; Jose Luis García-Klepzig (BMJ Open)
Introduction The main treatment for sleep apnoeas and hypopnoeas syndrome (SAHS) is continuous positive airway pressure (CPAP). However, patients sometimes do not adhere to the treatment protocol. Supplementary and complementary therapies have appeared as alternatives. Some of the therapies which are especially important are those related to myofunctional (MFT) and postural therapy (PT), as all of them are non-invasive, and their application is simpler than that of CPAP. We aim to present a protocol for a systematic review and meta-analysis for investigating new SAHS treatments, including the protocols and frequency of use and the effects they have on patient signs, symptoms and quality of life.Methods and analysis The literature search will be conducted using the Cochrane, Web of Science, Medline (via PubMed) and Scopus databases, from January 2020 to December 2020. All types of studies written in English and Spanish that investigate the use of alternative SAHS treatments related to MFT, or more importantly, the combination of MFT and PRT, will be selected. To evaluate their quality, the Critical Appraisal Checklist for Analytical Cross-Sectional will be applied. The primary factor valued in the studies will be the inclusion of MFT and PT reeducation in the treatment. Subgroup analyses will be carried out evaluating the specific type of treatments chosen and the improvements or deteriorations in the level of health and quality of life in the patients. Finally, several patient-related outcomes, namely sleep quality, quality of life and sleep Apnoeas and Hypoapnoeas Index, will be examined.Ethics and dissemination In this case, ethical approval is not necessary. The data used in the review will be exclusively obtained from published studies, implying there are no privacy concerns. The information obtained will be relevant to understand if the new treatments applied in SAHS are effective, and if postural and MFT therapy used together can be considered an appropriate approach to treat this disease.The results will be published in a peer-reviewed journal.